SENSOR APPLICATIONS IN ANALYSIS OF DRUGS AND FORMULATIONS - AKIFULHAQUE, M.; SHIVACHARAN, G. R.; PARVEEN, M. D.; PRIYA, D. K. SHANTHI; REDDY KONATHAM, TEJA KUMAR; VALLAKEERTHI, NARMADA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Several sensors, biosensors, and actuators are designed and mounted to analyze biomedical nutraceuticals, food, and nutraceutical products in this particular issue. Some applications concern classical subjects such as eubacteria determination in agricultural products, flashing material in foods such as the ethyl group’s chemicals, and fruit juices’ inhibitor properties. In contrast, the different applications are more revolutionary, such as safety research, the manufacture of artificial human senses (electronic nose or tongue), or t Ligands are often characterized by nano biosensors, utilizing biomaterials that involve specific aptamers, antibodies, enzymes, polymers, and sensory receptors. The square measurement of several modal sensing elements, integrated with nanomaterials, increases sensitivity such as nano biosensors and increases nano biosensor productivity. For the nano biosensor with increased efficiency, modality sensing components have been incorporated in this case. The square measurement of the elastic (ME) magnetic machine biosensors was used to classify infectious agents by a magnet coil in contemporary juice or milk and to develop direct detection of infectious agents on food scanning coils.